THE PRINCIPLE OF AUTONOMOUS INTERPRETATION AND LIMITS OF MEMBER STATES' COURTS IN INTERPRETING EU LAW - Marian GOCIU (Challenges of the Knowledge Society)
As EU law has become richer in terms of quantity and quality, the number of disputes which fall within the jurisdiction of the Member States’ courts has increased, as has the complexity of the issues raised by the parties to these disputes, in which provisions of Union law apply. Thus, the application of the provisions of EU law by national courts raises certain important issues, in particular with regard to the jurisdiction on interpreting EU law, which is a prerequisite for its application. Under art. 267 TFEU, the CJEU has jurisdiction to render a preliminary ruling concerning the interpretation of the Treaties and of legal acts of the institutions, bodies, offices or agencies of the Union. The aim of this study is to discover whether this article gives the CJEU exclusive jurisdiction to interpret Union law, or whether national courts also have such jurisdiction, in which cases they may interpret and apply Union law without resorting to the preliminary ruling mechanism. In the latter situation, we will identify the limits of this jurisdiction in relation to the principle of autonomous interpretation of Union law. The study can be a very useful instrument both for Romanian and Member States’ courts and other practitioners.